Gunslinger Girl - Ely, Lyndsay (New York : Little, Brown and Company, 2018)
In a post-Second Civil War lawless West, sharpshooter Serendipity "Pity" Jones stars in, and lives at, the Theater Vespertine, but there is a dark cost to her freedom that Pity may not be willing to pay.
"JIMMY Patterson Books."
Keywords: Gunfighters -- Fiction; Loyalty -- Fiction; Freedom -- Fiction; West (U.S.) -- Fiction; Science fiction